2022
DOI: 10.1002/jsfa.11767
|View full text |Cite
|
Sign up to set email alerts
|

Proteomic analyses of mitochondrial damage in postmortem beef muscles

Abstract: BACKGROUND The objective of the study was to examine the expression profiles of mitochondrial proteins in at‐death and 24 h postmortem (PM) using tandem mass tag (TMT) approach to characterize the mitochondria possible mechanisms that are affiliated with tenderization. RESULTS Results showed that the tender meat at 24 h PM emerged with more serious mitochondrial damage. Altogether 456 mitochondrial proteins were identified, including 442 down‐regulated and 14 up‐regulated proteins. These differentially‐express… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 49 publications
0
4
0
Order By: Relevance
“…The release of cytochrome c induces apoptosis [ 51 , 53 ]. Apoptosis is a proteolytic process related to meat tenderization under oxidative stress [ 49 , 54 , 55 ], which can result from increased mitochondrial membrane permeability [ 50 ]. Utrophin, encoded by UTRN, the hub gene of M1, is a therapeutic target for Duchenne muscular disease [ 56 , 57 ].…”
Section: Discussionmentioning
confidence: 99%
“…The release of cytochrome c induces apoptosis [ 51 , 53 ]. Apoptosis is a proteolytic process related to meat tenderization under oxidative stress [ 49 , 54 , 55 ], which can result from increased mitochondrial membrane permeability [ 50 ]. Utrophin, encoded by UTRN, the hub gene of M1, is a therapeutic target for Duchenne muscular disease [ 56 , 57 ].…”
Section: Discussionmentioning
confidence: 99%
“…Mitochondria were extracted referring to the approach described by Liu et al 14 . with minor modification.…”
Section: Methodsmentioning
confidence: 99%
“…Mitochondria were extracted referring to the approach described by Liu et al 14 with minor modification. The back muscles of samples were used to extract mitochondria.…”
Section: Extraction Of Mitochondriamentioning
confidence: 99%
“…However, there are few studies on mitochondrial inner membrane cristae structure in PM skeletal muscles. Our previous reports have demonstrated that Mic60, Mic19, and Mic27, which regulate cristae morphology and the growth of mitochondrial contact sites, showed a considerable decrease in expression at 24 h PM ( Liu et al, 2022 ). However, how the inner mitochondria's morphological control and cristae production work is still unknown.…”
Section: Introductionmentioning
confidence: 99%